Minority Carrier Properties of Microcrystalline Silicon Thin Films Grown by Hw-Cvd and Vhf-Pecvd Techniques - Okur, Salih; Göktaş, Oktay; Güneş, Mehmet; Güneş, Mehmet; Finger, Friedhelm; Okur, Salih; Carius, Reinhard (National Institute of Optoelectronics, 2005)
Opto-electronic properties of μc-Si:H films prepared by hot-wire/catalytic chemical vapor deposition (HWCVD) and very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD) techniques with various silane concentrations (SC) have been investigated using Raman spectroscopy, the steady-state photocarrier grating technique (SSPG), and the steady-state photoconductivity (SSPC). A correlation between the minority carrier transport properties and the microstructure has been found, using the dependence of the diffusion length (Ld) on the SC and Raman intensity ratio (I c RS) representing crystalline volume fractions. I C RS changes from 0.22 to 0.77. Ld increases with increasing Ic RS. It peaks around 0.5 with a maximum value of 270 nm, then decreases. Similar dependences of Ld on I C RS were obtained for films prepared by both HWCVD and VHF-PECVD. However, the grating quality factor measured on highly crystalline HWCVD films is substantially smaller than that found for VHF-PECVD films, indicating a relatively higher surface roughness present in the highly crystalline HWCVD films.
Keywords: Diffusion length; Microcrystalline silicon thin film; Raman spectroscopy; Steady state photocarrier grating technique; Silicon